A Study Of Corporate Governance Structure, Disclosure And Information Asymmetry In Indonesia Banking Industry - Jenny Sihombing; Hisar Pangaribuan (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
Thepurposesof thisstudyare to find out the effect of corporate governancestructure on information asymmetry, to find out the effect of corporate governancestructure on disclosure, and to find outtheeffect of disclosure on information asymmetryin Indonesia banking industry.This studyused partial least square/ variance basedstatistical method.Theresultsof this studyfound outthatgood implementation ofcorporate governance structurewill increasedisclosure in Indonesia banking industry.Theother result implied that the higher implementation disclosurewill reduceinformationasymmetry in Indonesia banking industry (disclosurerepresentedby the indicator ofpercentage corporate governance items disclosed or as IPCG).